Entrepreneurial Assistance for Students of Muhammadiyah High School Through Social Media Marketing and Product Photo Styling Workshop - Iqbal Ramadhani Fuadiputra; Kardina Yudha Parwati; Fika Fitriasari (Indonesian Journal of Cultural and Community Development, 2021)
SMA Muhammadiyah 1 is a senior secondary education institution under the auspices of the Muhammadiyah Foundation. SMA Muhammadiyah 1 Malang always aligns the school learning curriculum with the vision, mission, and goals of the school as well as the competencies of the planned graduates. One example is the holding of entrepreneurship laboratory subjects. This entrepreneurship subject aims to provide entrepreneurial skills and instill an entrepreneurial spirit in SMA Muhammadiyah 1 Malang students. In this subject, students are taught about the entrepreneurial spirit and traits such as persistence, independence, creativity, innovation, independence and so on. Students are also provided with skills in making products by teachers who teach entrepreneurship subjects. Based on the process of situation analysis, the servant found that the activities of entrepreneurship courses at SMA Muhammadiyah 1 Malang in the aspect of product manufacture had been going well, but partners experienced problems in marketing communication activities for the products that had been produced. The purpose of the implementation of this service program is to provide knowledge and improve student skills in marketing communication of products resulting from entrepreneurial subjects at SMA Muhammadiyah 1 Malang. In this service, the service will carry out a social media marketing workshop and photo styling products. Through this service program it is hoped that students of SMA Muhammadiyah 1 Malang will have technical skills in the aspect of product marketing so that when they graduate they have additional skills for entrepreneurship.